Imperative Secretes Of Comestibles In Ayurveda W.S.R. To Ashta Ahara Vidhi Visheshayatana. - Jolly, Neha; Sharma, Punita; Samagandi, Kashinath (International Research Journal of Ayurveda & Yoga, 2021)
Annam Vritikaranam Shrestam” Ahara is the most essential demand necessary for the sustenance of human life. Food acts as a spur for body development, transformation and health maintenance. Ancient classics emphasize the importance of wholesome food responsible for the complexion, pleasant voice, longevity, nourishment, and happiness of the human. Ahara is one of the significant Upastambha of the body that mainly pivot on the knowledge of dietetics. Congenial and uncongenial effects of food depend upon these eight factors of diet defined as Astha Ahara Vidhi Visheshayatana .If the rules and regulations explained under these factors, adopted properly will result in well being of the person otherwise leads to the manifestation of varied diseases. Acharyas has explained the eight factors of diet, determining the detergence of Ahara . The present paper highlighting the concept of Astha Ahara Vidhi Visheshayatana and also throws light on the significance of Food nature, Food processing methods, Tropology, Quantity of food intake, and Rules of eating.